Naomi the rainbow glitter dragon - Mara, Maddy; Damiao, Thais (New York, NY Scholastic Inc., 2021)
"Naomi loves being a Glitter Dragon Girl. She can fly above treetops and roar glittery bursts of magic. Best of all, she and the other Glitter Dragons are keeping their beloved Magic Forest safe from the Shadow Sprites. But all is not as it seems in this special place. The Shadow Sprites' power is growing. . . and they may not be alone. Naomi must harness all the dragon magic she's learned to lead the Glitter Dragon Girls against this new threat"--
Reading Level: Grade 3.
Appeals to 2nd-3rd Graders.
Keywords: Dragons -- Juvenile fiction; Magic -- Juvenile fiction; Friendship -- Juvenile fiction; Girls -- Juvenile fiction; Good and evil -- Juvenile fiction; Dragons -- Fiction; Magic -- Fiction; Friendship -- Fiction; Dragons -- Romans, nouvelles, etc. pour la jeunesse; Amitie -- Romans, nouvelles, etc. pour la jeunesse; Dragons; Friendship; Magic; Novels; Novels; Fantasy fiction; Fiction; Juvenile works; Fantasy fiction; Fantasy fiction